A note on Bitcoin’s price volatility - Ahmad Farid Abdul Hamid; Ameen Ali Talib (University of Merdeka Malang, 2019)
Cryptocurrencies such as bitcoin are sometimes referred to as the new gold and the buzz that surrounded bitcoins in the last few years is akin to the old day’s gold rush. Cryptocurrencies are not directly linked to any monetary policy instruments or fundamentals. Therefore, the analysis of common factors between these virtual currencies and other ﬁnancial asset classes is challenging. Towards the end of 2017, Bitcoin’s price shot up to record high figures as cryptocurrency was gaining popularity not only for transactions but also for investments. This motivated us to investigate the relationship bitcoin prices have with Gold and stock index and crude oil. Historical prices were gathered from the start of 2017 to the end of the year, the Pearson’s Correlation analysis was chosen to study the relationship of Bitcoin and 3 other economic indicators namely gold, crude oil, and stock market prices. Then we did a multiple regression. Bitcoin has a correlation coefficient of 0.966 when compared to the stock market index SP 500 which means that they both share similar properties and characteristics. The t statistic for each variable was also significant. This is paper explores the possible factors that are correlated with the surge in bitcoin prices and offers views on the relevance of bitcoin in today’s world.JEL Classification: F62, G14, G15DOI: https://doi.org/10.26905/jkdp.v23i3.3103